PEMAHAMAN ATAS SAP SEBAGAI PEMODERASI PENGARUH AKUNTABILITAS DAN TRANSPARANSI PADA KINERJA ANGGARAN SKPD KOTA DENPASAR - Arista, A.A Sagung Ary Nur; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 17 No 2 (2016), 2016)
This study was to determine the effect of accountability and transparency in the budget with the understanding of the performance of government accounting standards as a moderating variable. The theory used in this research that is agency theory. Research was conducted on the local work unit Denpasar. The study sample as many as 33 SKPD and determined by total sampling method. The data collection was conducted by questionnaire. Data analysis techniques used the Multiple Linear Regression and Moderated Regression Analysis (MRA). The results of this study indicate Accountability and transparency positive effect on the performance of the budget. The study also showed that the understanding of the possibilities of government accounting standards weaken the influence of accountability on budget performance. While the test results moderation understanding of government accounting standards with transparency show an understanding of government accounting standards strengthen the effect of transparency on budget performance.
Keywords: Understanding of SAP, accountability, transparency, budget performance